PERANCANGAN WEBSITE APLIKASI PENJUALAN RESTORAN AYAM KEPRABON - Ignatius Adrian Mastan (JBASE - Journal of Business and Audit Information Systems, 2019)
The development of information technology has increased in all aspects of human life. All human activities today have used information technology and are getting easier, one of which is the transaction of ordering food in restaurants. Buyers do not need to come to the restaurant to make a purchase transaction, by using a smartphone they can open a website to order and buy food by online. With the increasingly sophisticated information technology, every business must be able to compete with success in the same business so as not to be left behind and displaced by others.The restaurant that needs this sales application is the Ayam Keprabon Restaurant. Ayam Keprabon Restaurant has 45 outlets in several cities, namely: Jakarta, Depok, Tangerang, South Tangerang, Bekasi, and Bogor. With this Website-Based Sales Application, buyers can view restaurant profiles, food & beverage menus, make orders, make payments, check order delivery status, register new members, place reservations. With this site-based sales application, it can increase sales and increase the competitiveness of Ayam Keprabon Restaurant with competitors who have implemented information technology in their business.